SOCIO PSYCHOLOGICAL ANALYSIS ON NIKKI-ROSSA'S CONTEMPORARY POEM (by NIKKI GIOVANNI A BLACK AMERICAN POET) - Danti Pudjianti (Buletin Al-Turas, 2004)
Reading short stories, novels, poems, or watching the play performance Is a very clear example of literary appreciation found in neighboring daily life. Producing and writing about literary topics or work is entitled a creative activity. It Is called a creative one because of writing whose the meaning of composing something in written needs much thinking to complete. Appreciating the literary works means doing the action to have intercourse with the creation of literature wholeheartedly.